2022
DOI: 10.1128/mbio.02906-21
|View full text |Cite
|
Sign up to set email alerts
|

Hamsters Expressing Human Angiotensin-Converting Enzyme 2 Develop Severe Disease following Exposure to SARS-CoV-2

Abstract: The rapid emergence of SARS-CoV-2 has created a global health emergency. While most human SARS-CoV-2 disease is mild, some people develop severe, life-threatening disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 48 publications
1
31
1
Order By: Relevance
“…RNA in the CNS as well as inflammation and changes in the neurovascular system [17,30]. Although the Syrian hamster has been used most frequently in hamster studies, it was recently shown that, in Roborovski dwarf hamsters, inbred hamsters, transgenic hamsters expressing human ACE2, and obese hamsters, SARS-CoV-2 infection resulted in more severe disease and systemic spread, including virus spread to the CNS [88][89][90][91].…”
Section: Trends In Neurosciencesmentioning
confidence: 99%
“…RNA in the CNS as well as inflammation and changes in the neurovascular system [17,30]. Although the Syrian hamster has been used most frequently in hamster studies, it was recently shown that, in Roborovski dwarf hamsters, inbred hamsters, transgenic hamsters expressing human ACE2, and obese hamsters, SARS-CoV-2 infection resulted in more severe disease and systemic spread, including virus spread to the CNS [88][89][90][91].…”
Section: Trends In Neurosciencesmentioning
confidence: 99%
“…In some models such as hACE2 hamsters, pulmonary lesions are localized predominantly in bronchi and bronchioles, whereas in other models such as hACE2 mice, the lesions are predominantly in the alveoli. 27 Although pulmonary vascular changes do occur including endothelial damage/endotheliitis, vasculitis, microthrombi, and NETs, the severity of these findings are generally limited in animal models. Virus cytopathic-like changes observed in animal models can also be associated with regeneration of injured airway epithelium and need further characterization by IHC/ISH and/or ultrastructural evaluation for confirmation.…”
Section: Covid-19 Pathophysiology and Disease Phenotypes In Animal Mo...mentioning
confidence: 99%
“… 10 , 25 Damage (inflammation and necrosis) to olfactory epithelium as well as respiratory epithelium of the nasal cavity is observed in hACE2-expressing mouse and hamster models. 13 , 27 …”
Section: Covid-19 Pathophysiology and Disease Phenotypes In Animal Mo...mentioning
confidence: 99%
See 2 more Smart Citations